“Two Stones on One Bird”: A Case Report on Severe Biphasic Anaphylaxis Masquerading as Life-Threatening Acute Asth - Alvin Oliver Payus; Azliza Ibrahim; Norlaila Mustafa (2018)
BACKGROUND: Anaphylaxis often misdiagnosed and treated as acute asthma, especially when it has a predominant respiratory symptom, and there are no obvious precipitants or previous allergic history. This morbid outcome is preventable if the level of suspicion for anaphylaxis is high among healthcare provider when treating a patient who is not responding to the standard management of acute asthma. A proportion of anaphylactic patient shows a biphasic reaction which potentially fatal when it is under-anticipated and prematurely discharge without adequate observation period after the recovery of the initial episode. CASE REPORT: Here, we present a case of a young man who has childhood asthma with the last attack more than 10years ago presented with symptoms suggestive of acute exacerbation of bronchial asthma. As the symptoms failed to improve after standard asthma management, anaphylaxis was suspected, and he was given intramuscular adrenaline 0.5 mg which leads to symptom improvement. However, he developed another attack shortly after improvement while under observation. CONCLUSION: The objective of this case report is to emphasis the importance of keeping anaphylaxis in mind whenever a patient has treatment-refractory asthma, and also the anticipation of biphasic reaction that warrants adequate observation period especially those who are likely to have developed it.